Old Women: Divination and Magic or anus in Roman Literature - Migdał, Justyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2014)
Word anus was used in a primarily negative sense to describe an old woman. Anus is usually presented as a libidinous and hideous hag who indulges in strong wine or practices black magic, mainly for erotic purposes. Though Latin literature brings as well examples of a different type of anus: goddesses assuming the shape of old women to guide or deceive the mortals and old prophetic women, inspired by the gods. Anus can be gifted with divine powers and secret knowledge. The paper traces the motif of anus as a witch or a divine woman on the basis of selected examples from the works of Horace, Ovid, Petronius, Apuleius and Silius Italicus.